Un metodo senza donne. La filosofia si alleò con la geometria e perse le emozioni - Amalfitano, Elisabetta (Il sogno della farfalla, 2008)
The article takes into consideration the period of the Scientific Revolution, when rational thought and the experimental method impose themselves on the philosophical scene excluding a priori sensitivity and imagination and imposing a logical-rational perspective as unique and absolute. The 1600s sees women emerge on the cultural and public scene: in Europe five queens govern, in Paris the precieuses impose themselves in the salons and women become the privileged interlocutors of the philosophers. Analyzing in particular the correspondence between Princess Elisabeth of Bohemia and Descartes, the article tends to highlight how the philosopher imposes an absolute dominion if not annulment on everything which is not rational. Passions, sensations, emotions must be banished in order to reach “beatitude”. It is Spinoza who radicalizes this rationalism revealing an alliance with religious thought. Philosophy, allying itself to geometry, tries to extend the scientific method to the human context, but in so doing, it loses altogether that sensitivity, that imagination which would have allowed it to go beyond the visible and measurable.